2022
DOI: 10.1530/etj-22-0005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Sars-Cov-2 antigens in thyroid gland showing histopathological features of subacute thyroiditis

Abstract: Clinical and laboratory findings of subacute thyroiditis have been repeatedly reported as being associated with acute Sars-Cov-2 infection and post- COVID-19 syndrome. Exact mechanisms and histopathological correlates underlying thyroid involvement remained unresolved, but current insights suggest either direct viral damage, systemic inflammatory reaction, or an autoimmune response as possible noxious effectors. Here we present findings of immunohistochemical/immunofluorescence detection of Sars-Cov-2 viral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Furthermore, many patients with painless SAT were in intensive care unit and/or were suffering from severe forms; it is conceivable that many of them were unable to report pain because of their general condition and treatment. The recent finding of a copious mononuclear infiltrate forming granuloma-like structures with giant multinucleated cells, resembling those observed in previous cases of SAT, in the thyroid tissue obtained from a patient deceased from COVID-19 is against the hypothesis of a reduced lymphocytic and plasmocytic infiltration of the thyroid, resulting from lymphopenia [45]. Among patients described in this paper, most were treated with glucocorticoids, with an excellent symptomatic response, a result similar to that reported in SAT described in the pre-COVID period.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, many patients with painless SAT were in intensive care unit and/or were suffering from severe forms; it is conceivable that many of them were unable to report pain because of their general condition and treatment. The recent finding of a copious mononuclear infiltrate forming granuloma-like structures with giant multinucleated cells, resembling those observed in previous cases of SAT, in the thyroid tissue obtained from a patient deceased from COVID-19 is against the hypothesis of a reduced lymphocytic and plasmocytic infiltration of the thyroid, resulting from lymphopenia [45]. Among patients described in this paper, most were treated with glucocorticoids, with an excellent symptomatic response, a result similar to that reported in SAT described in the pre-COVID period.…”
Section: Discussionsupporting
confidence: 61%
“…Importantly, histopathological studies have suggested that virus infiltration in endocrine glands can be observed in severe cases of COVID-19. Such studies have detected the viral genome and proteins inside endocrine tissues and have identified signs of apoptosis as a result of this viral invasion ( 54 , 55 ), which signifies the potential for direct damage to the thyroid gland in severe COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of the angiotensin-converting enzyme-2 (ACE2) receptor used by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to enter the cell in thyroid follicular cells suggests that COVID-19 may directly cause inflammation in thyroid cells [19][20][21]. The finding of SARS-CoV-2 antigens in the thyroid gland showing the histopathological features of SAT in a post-mortem examination also strengthens this hypothesis [22]. However, considering that SAT often develops following viral infections, the molecular mimicry hypothesis also comes to the fore.…”
Section: Discussionmentioning
confidence: 86%